A long-lasting porcine model of ARDS caused by pneumonia and ventilator-induced lung injury - Enric Barbeta; Marta Arrieta; Ana Motos; Joaquim Bobi; Hua Yang; Minlan Yang; Giacomo Tanzella; Pierluigi Di Ginnatale; Stefano Nogas; Carmen Rosa Vargas; Roberto Cabrera; Denise Battaglini; et al. (Critical Care, 2023)
Abstract Background Animal models of acute respiratory distress syndrome (ARDS) do not completely resemble human ARDS, struggling translational research. We aimed to characterize a porcine model of ARDS induced by pneumonia—the most common risk factor in humans—and analyze the additional effect of ventilator-induced lung injury (VILI). Methods Bronchoscopy-guided instillation of a multidrug-resistant Pseudomonas aeruginosa strain was performed in ten healthy pigs. In six animals (pneumonia-with-VILI group), pulmonary damage was further increased by VILI applied 3 h before instillation and until ARDS was diagnosed by PaO2/FiO2 < 150 mmHg. Four animals (pneumonia-without-VILI group) were protectively ventilated 3 h before inoculum and thereafter. Gas exchange, respiratory mechanics, hemodynamics, microbiological studies and inflammatory markers were analyzed during the 96-h experiment. During necropsy, lobar samples were also analyzed. Results All animals from pneumonia-with-VILI group reached Berlin criteria for ARDS diagnosis until the end of experiment. The mean duration under ARDS diagnosis was 46.8 ± 7.7 h; the lowest PaO2/FiO2 was 83 ± 5.45 mmHg. The group of pigs that were not subjected to VILI did not meet ARDS criteria, even when presenting with bilateral pneumonia. Animals developing ARDS presented hemodynamic instability as well as severe hypercapnia despite high-minute ventilation. Unlike the pneumonia-without-VILI group, the ARDS animals presented lower static compliance (p = 0.011) and increased pulmonary permeability (p = 0.013). The highest burden of P. aeruginosa was found at pneumonia diagnosis in all animals, as well as a high inflammatory response shown by a release of interleukin (IL)-6 and IL-8. At histological examination, only animals comprising the pneumonia-with-VILI group presented signs consistent with diffuse alveolar damage. Conclusions In conclusion, we established an accurate pulmonary sepsis-induced ARDS model.